Integrated analysis of pediatric glioblastoma reveals a subset of biologically favorable tumors with associated molecular prognostic markers - Korshunov, Andrey; Sturm, Dominik; Capper, David; Meyer, Jochen; Schrimpf, Daniel; Milde, Till; Witt, Olaf; Kulozik, Andreas; Deimling, Andreas von; Pfister, Stefan (Acta neuropathologica, 2015)
Pediatric glioblastoma (pedGBM) is amongst the most common malignant brain tumors of childhood and carries a dismal prognosis. In contrast to adult GBM, few molecular prognostic markers for the pediatric counterpart have been established. We, therefore, investigated the prognostic significance of genomic and epigenetic alterations through molecular analysis of 202 pedGBM (1-18 years) with comprehensive clinical annotation. Routinely prepared formalin-fixed paraffin-embedded tumor samples were assessed for genome-wide DNA methylation profiles, with known candidate genes screened for alterations via direct sequencing or FISH. Unexpectedly, a subset of histologically diagnosed GBM (n = 40, 20 %) displayed methylation profiles similar to those of either low-grade gliomas or pleomorphic xanthoastrocytomas (PXA). These tumors showed a markedly better prognosis, with molecularly PXA-like tumors frequently harboring BRAF V600E mutations and 9p21 (CDKN2A) homozygous deletion. The remaining 162 tumors with pedGBM molecular signatures comprised four subgroups: H3.3 G34-mutant (15 %), H3.3/H3.1 K27-mutant (43 %), IDH1-mutant (6 %), and H3/IDH wild-type (wt) GBM (36 %). These subgroups were associated with specific cytogenetic aberrations, MGMT methylation patterns and clinical outcomes. Analysis of follow-up data identified a set of biomarkers feasible for use in risk stratification: pedGBM with any oncogene amplification and/or K27M mutation (n = 124) represents a particularly unfavorable group, with 3-year overall survival (OS) of 5 %, whereas tumors without these markers (n = 38) define a more favorable group (3-year OS ~70 %).Combined with the lower grade-like lesions, almost 40 % of pedGBM cases had distinct molecular features associated with a more favorable outcome. This refined prognostication method for pedGBM using a molecular risk algorithm may allow for improved therapeutic choices and better planning of clinical trial stratification for this otherwise devastating disease.